Managing the attributes of pilot errors in the process of redevelopment of Marine Pilot Reliability Index (MPRI): a systematic literature review - Tiong, Kuong Chiing; Adam, Nor Mariah; Marzuki, Omar Faruqi; Teo, Ellie Yih Lih; Wong, Tze Jin (Human Resource Management Academic Research Society, 2021)
Ships manoeuvring in confined waters of a harbour were required to make used of the services of an experienced pilot equipped with nautical skills to prevent maritime accidents. However, there are not many formal studies on the risks or pilot errors and human reliability of the pilotage. The probability of the ship’s collision without a pilot on board is about nine (9) times higher than those engaged a pilot. The objective of this paper is to evaluate the pilot errors, improving pilot reliability and their competencies. This paper reviews and categorizes the literature published about the problems associated with pilot’s risk and error in pilotage, to improve the reliability of the pilot. This will cover the review of the recent published literatures on marine pilot’s reliability. This paper hope to shine the vital roles of safe pilotage and towage services and determine the efficiency and productivity of any ports. By the end of this research, it is hope that it is possible to improve the generic model to reduce or eliminate all possible human error or pilots’ risk and improve the reliability and competencies of pilots using the improved version of Marine Pilot’s Reliability Index (MPRI).